2012
DOI: 10.1037/a0024582
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive mechanisms of false facial recognition in older adults.

Abstract: Older adults show elevated false alarm rates on recognition memory tests involving faces in comparison to younger adults. It has been proposed that this age-related increase in false facial recognition reflects a deficit in recollection and a corresponding increase in the use of familiarity when making memory decisions. To test this hypothesis, we examined the performance of 40 older adults and 40 younger adults on a face recognition memory paradigm involving three different types of lures with varying levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 21 publications
2
33
0
2
Order By: Relevance
“…The impact that negative information has on motivation and decision strategies is in need of further research. Additionally, we replicated previous findings that older adults are more likely to engage in familiarity-based processing rather than itemspecific processing during memory retrieval (Badham et al, 2012;Bastin & Van der Linden, 2003;Edmonds et al, 2011;Howard et al, 2006;Jennings & Jacoby, 1997;Schacter, et al, 1997). Increased use of item-specific information is associated with enhanced recognition performance (Engelkamp, Biegelmann, & McDaniel, 1998;McCabe, Presmanes, Robertson, & Smith, 2004), but the effect size was relatively small.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The impact that negative information has on motivation and decision strategies is in need of further research. Additionally, we replicated previous findings that older adults are more likely to engage in familiarity-based processing rather than itemspecific processing during memory retrieval (Badham et al, 2012;Bastin & Van der Linden, 2003;Edmonds et al, 2011;Howard et al, 2006;Jennings & Jacoby, 1997;Schacter, et al, 1997). Increased use of item-specific information is associated with enhanced recognition performance (Engelkamp, Biegelmann, & McDaniel, 1998;McCabe, Presmanes, Robertson, & Smith, 2004), but the effect size was relatively small.…”
Section: Discussionsupporting
confidence: 75%
“…Research has shown that participants engage in more item-specific compared to familiarity-based processing when they have adopt a relatively conservative response criteria at test (Israel & Schacter, 1997;Schacter, Israel, & Racine, 1999). Additionally, older adults are more likely to engage in familiarity-based processing rather than item-specific processing during memory retrieval (Badham et al, 2012;Bastin & Van der Linden, 2003;Edmonds et al, 2011;Howard et al, 2006;Jennings & Jacoby, 9 1997;Schacter, Koutstaal, Johnson, Gross, & Angell, 1997). Therefore, we expected that older adults in the present study would engage in more familiarity-based processing than item-specific processing compared to young adults.…”
mentioning
confidence: 99%
“…Similar to the neuropsychological explanations offered to account for memory distortions in frontal patients, false facial recognition in older individuals has been attributed to an age-related deficit in context recollection and a corresponding increase in the use of familiarity when making face memory decisions [1,3,47,64,74]. Furthermore, it has been suggested that the context-recollection deficit responsible for the increased susceptibility of older adults to face memory illusions reflected an age-related decline in frontal lobe function [5,18,64]. This theoretical formulation is consistent with other evidence that automatic memory processes such as familiarity remain relatively invariant with age while more controlled memory processes such as recollection and source monitoring show agerelated decline [28,30,33,76,83], and also with neuroimaging studies demonstrating prominent changes in frontal lobe structural/functional integrity with increasing age [8,15,27,78].…”
Section: Face Memory Distortions In Cognitively Intact Older Adultsmentioning
confidence: 88%
“…To test the context-recollection deficit hypothesis of the age-related increase in face memory distortions, we [18] recently conducted a study comparing the performance of 40 old (mean age = 74.0, range = 63-86) and 40 young (mean age = 20.8, range = 18-28) cognitively intact adults on a face memory paradigm originally developed by Bartlett et al [5]. This recognition memory task included three different types of distractor items with varying levels of familiarity: "familiarized lures" that were exact repetitions of faces that participants were exposed to in a personality rating task conducted prior to the presentation of the study list, "conjunction lures" that were synthetic faces created by recombining the inner regions (eyes, nose, and mouth) and the outer regions (hair, ears, and jaw line) from two different study faces, and entirely new faces.…”
Section: Face Memory Distortions In Cognitively Intact Older Adultsmentioning
confidence: 99%
“…Much research has been conducted on the use of familiarity as a means for making identifications, and this process appears automatic. For this reason, facial recognition based on familiarity by aging adults remains intact even when recollection fails and they are unable to recall the specific context in which the face was viewed [12].…”
Section: What Did You See?mentioning
confidence: 99%